Perivascular cell‐derived extracellular vesicles stimulate colorectal cancer revascularization after withdrawal of antiangiogenic drugs. Issue 7 (21st May 2021) - Huang, Maohua; Chen, Minfeng; Qi, Ming; Ye, Geni; Pan, Jinghua; Shi, Changzheng; Yang, Yunlong; Zhao, Luyu; Mo, Xukai; Zhang, Yiran; Li, Yong; Zhong, Jincheng; et al.
Abstract: Antiangiogenic tyrosine kinase inhibitors (AA‐TKIs) have become a promising therapeutic strategy for colorectal cancer (CRC). In clinical practice, a significant proportion of cancer patients temporarily discontinue AA‐TKI treatment due to recurrent toxicities, economic burden or acquired resistance. However, AA‐TKI therapy withdrawal‐induced tumour revascularization frequently occurs, hampering the clinical application of AA‐TKIs. Here, this study demonstrates that tumour perivascular cells mediate tumour revascularization after withdrawal of AA‐TKI therapy. Pharmacological inhibition and genetic ablation of perivascular cells largely attenuate the rebound effect of CRC vascularization in the AA‐TKI cessation experimental settings. Mechanistically, tumour perivascular cell‐derived extracellular vehicles (TPC‐EVs) contain Gas6 that instigates the recruitment of endothelial progenitor cells (EPCs) for tumour revascularization via activating the Axl pathway. Gas6 silence and an Axl inhibitor markedly inhibit tumour revascularization by impairing EPC recruitment. Consequently, combination therapy of regorafenib with the Axl inhibitor improves overall survival in mice metastatic CRC model by inhibiting tumour growth. Together, these data shed new mechanistic insights into perivascular cells in off‐AA‐TKI‐induced tumour revascularization and indicate that blocking the Axl signalling may provide an attractive anticancer approach for sustaining long‐lasting angiostatic effects to improve the therapeutic outcomes of antiangiogenic drugs in CRC.